Pengaruh Struktur Modal dan Efisiensi Aset Terhadap Nilai Perusahaan Transportasi dan Logistik Di Bursa Efek Indonesia - Daffa Ardiansyah; Diva Tasya; Febby Renata; Ade Hidayatullah; Linawati Linawati (Prisani Cendekia, 2026)
This study aims to analyze the effect of capital structure (DER) and asset efficiency (ROA) on firm value (PBV) in the transportation and logistics sector listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employs a quantitative approach using panel data regression analysis and applies the Chow test, Hausman test, and Lagrange Multiplier (LM) test to determine the most appropriate estimation model. The results indicate that capital structure does not have a significant effect on firm value. In contrast, asset efficiency has a positive and significant effect on firm value. Simultaneously, capital structure and asset efficiency have a significant effect on firm value, although their explanatory power is relatively moderate, with an adjusted R² of 38.87%. These findings highlight the importance of efficient asset management in enhancing firm value, while debt-based financing decisions need to be managed cautiously, as they do not show a significant impact during the period under study